SHOULD ECOLOGICAL ENTREPRENEURS IGNORE THE EQUITY OF DEVELOPMENT? INSIGHTS FROM THE SATYAMEV JAYATE WATER CUP BY PAANI FOUNDATION - Dash, Dr. Amarendra Kumar; Dash, Dr. Rajendra Kumar; Behera, Dr. Rashmi Ranjan; Nath, Bibha Rani (The journal of contemporary issues in business and government, 2023)
What should be the right approach to water harvesting and management: (1) convenience,(2) prudence, or (3) the integration of both? The convenience approach refers to the tendency of governments and organizations to focus largely on increasing the supply of water without telling citizens to use water rationally. The prudence approach insists on the minimal and judicious use of water, something governments seldom tell citizens for the fear of losing popularity. The integration approach absorbs the best methods and technology available to intervene in the supply as well as demand side of water. With a focus on the integration approach, this study undertakes a case analysis of the Satyamev Jayate Water Cup (SJWC) by Paani Foundation that converted many draught-prone regions of the Maharashtra state of India into water-sufficient and prosperous zones by utilizing low-cost, indigenous knowledge systems and eco-friendly measures. The study aims to highlight the limitations of this massive socio-ecological campaign in the context of water management and governance.